2011
DOI: 10.1128/aem.02879-10
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium Availability Affects the Ratio of Ammonia-Oxidizing Bacteria to Ammonia-Oxidizing Archaea in Simulated Creek Ecosystems

Abstract: The ammonia-oxidizing microbial community colonizing clay tiles in flow channels changed in favor of ammonia-oxidizing bacteria during a 12-week incubation period even at originally high ratios of ammoniaoxidizing archaea to ammonia-oxidizing bacteria (AOB). AOB predominance was established more rapidly in flow channels incubated at 350 M NH 4 ؉ than in those incubated at 50 or 20 M NH 4 ؉ . Biofilm-associated potential nitrification activity was first detected after 28 days and was positively correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 43 publications
8
53
0
Order By: Relevance
“…Furthermore, community analysis of ammonia-oxidizing prokaryotes in freshwater sediments and soils indicated a numerical predominance of AOA at low ammonium concentrations (18,29) and a positive effect of ammonium availability on the population size of AOB (53). Similar effects have been observed in natural and simulated small creek ecosystems with different ammonium concentrations (30). However, it is uncertain how temperature will affect the AOB dominance observed at relatively high ammonium availability, as well as the AOB and AOA community structures.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Furthermore, community analysis of ammonia-oxidizing prokaryotes in freshwater sediments and soils indicated a numerical predominance of AOA at low ammonium concentrations (18,29) and a positive effect of ammonium availability on the population size of AOB (53). Similar effects have been observed in natural and simulated small creek ecosystems with different ammonium concentrations (30). However, it is uncertain how temperature will affect the AOB dominance observed at relatively high ammonium availability, as well as the AOB and AOA community structures.…”
supporting
confidence: 49%
“…Metagenomic studies have shown that members of the kingdom Crenarchaeota (or Thaumarchaeota, as recently proposed [13,63]) within the domain Archaea also contain the amo genes (69,70), and subsequent studies have demonstrated the existence of ammonia-oxidizing archaea (AOA) (58). The numerical dominance of amoA-containing Archaea in soils (43) and in aquatic environments (30,47), their distribution worldwide (24), and the capacity of enrichments of Archaea and isolates to oxidize ammonia (17,28,34) raise questions regarding their relevance to ammonia oxidation in freshwater environments and, specifically, within epilithic stream biofilms.…”
mentioning
confidence: 99%
“…Studies addressing the effect of flow intermittency on archaeal communities are scarce compared to those with bacteria, and this can be taken as an indication that Archaea constitute a minor component of streambed microbial communities. Even in permanent rivers and streams Bacteria outnumber Archaea in all streambed compartments (Battin et al, 2001;Herrmann et al, 2011;Merbt et al, 2011Merbt et al, , 2015Buriánková et al, 2013), but is also true that Archaea occur in arid soils, microbial mats and freshwater sediments exposed to desiccation (Rothrock and (Rothrock and Garcia-Pichel, 2005;Soule et al, 2009;Timonen and Bomberg, 2009;Conrad et al, 2014). Despite this information, no conclusive data on the ecological function of the Archaea in streambeds are available.…”
Section: Structural Changes and Adaptations Of Biofilms To Dry And Wementioning
confidence: 88%
“…Finally, nitrite reductase has been proposed to be involved in detoxification of nitrite in AOB cultures (Beaumont et al, 2002;Cantera and Stein, 2007a). Nitrite detoxification has yet to be examined in AOA cultures, but AOA are generally more competitive in low-ammonia environments (Martens-Habbena et al, 2009;Di et al, 2010;Herrmann et al, 2011) where nitrite concentrations are unlikely to reach toxic levels.…”
Section: Introductionmentioning
confidence: 99%